Pemanfaatan Limbah Tempurung Kelapa Muda sebagai Alternatif Material Akustik: Susilo Indrawati, Suyatno - Susilo Indrawati Susilo Indrawati; Suyatno Suyatno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
This research will utilize coco shell as an acoustic tile, specifically resonator so that a coco shell has a better value. Coco shell used will be a young coco shell, since its a rarely utilized waste. The resonator will be tested in regard of its ability to absorb and scatter sound. This research consists of a test to determine the value of the absorption coefficient of the material, the scattering pattern panel, and the determination coefficient scattering. The purpose of this research in addition resonator has aesthetic value currency will also have more value in the acoustic space. Acoustic room means a room that requires special treatment in acoustic music studio room, for example, broadcast, places of worship, home theatre, music chamber, and others. The absorption coefficient for convex shell has greater value than the concaves, especially at a frequency of 1000 Hz and 4000 Hz. Perforate addition in the convex shell makes the scattering pattern smoother. The addition of sugar cane pulp has the same scattering pattern. The scattering coefficient has a negative values exception at a frequency of 500 Hz, especially for acoustic panels are arranged in convex and convex panels that filled by bagasse. When the measurement in an anechoic chamber, the result says that panels made from young coconut shell either arranged convex and concave above can reduce the frequency of 1500 Hz. there is perforation/hole on the composition of convex shell panels capable of lowering the level of pressure above 1000 Hz.